Reliability and validity of the Objective Structured Clinical Assessment (OSCA) in undergraduate nursing program - Nurumal, Mohd. Said; Aung, Khin Thandar; Ismail, Sakinah (Akademia Baru, 2016)
Clinical assessment is the one of the essential components in assessing student’s competency in nursing curriculum. There are various types of clinical assessment to measure the competency level of skills in nursing students. Nevertheless, the reliability and validity of the assessment is still unclear in the area of skill assessment, problem solving, knowledge and patient management. Objective structure clinical Examination (OSCE) is a reliable and valid method in evaluating nursing students’ clinical skill. However, problems with regard the OSCEs appeared because the assessment only focusing on the dexterity rather than focusing on the holistic care to the patient. Therefore, new method approach, objective structure clinical assessment (OSCA) was established. This study sought to identify the extent of reliability and validity of this OSCA assessment in the Faculty of Nursing at International Islamic University Malaysia (IIUM). The applicability of this assessment OSCA was also explored by assessing immediate nursing students' feedback regarding this exam. A total of 53 nursing students from the final year was drawn from a purposive random sampling. A self-developed checklist of procedures and feedback questionnaire adapted from another well-known OSCA’s study was used as research instruments. The results showed that there is a statistically significant positive correlation between the two examiners in all stations (rs of station 1=0.968; p=0.0001, rs of station 2=0.811; p=0.0001 and rsof station 3=0.728; p=0.005, rs of station 4=0.837; p= 0.003). Moreover, the reliability of the OSCA stations was measured using Cronbach α to evaluate the internal consistency of each station. The internal consistency of OSCA stations was statistically significant and highly reliable as Cronbach α was higher than 0.7 in three stations among four exam stations. The findings indicated that the OSCA examination was a reliable and valid method in assessing undergraduate nursing students. The running cost of the OSCA is outweighed by the educational benefits, examiners’ satisfaction as well as students’ satisfaction.